THE ROLE OF ROMANIAN MANAGERS PERSONALITY IN CHOOSING A LEADERSHIP STYLE, A COMPARATIVE APPROACH - Maria-Elena, GHEORDUNESCU (Strategii Manageriale, 2014)
Managers are that empowered group of people, specially trained, who direct, coordinate and direct the work of all members of an organization. Managers are those specialists who can make decisions with a large impact on the business activity. No matter the activity profile or size, companies need good managers, who are able to adapt to the specific economic conditions of our times. This paper aims to study the personality of three managers from Romania, who working in the field of road transport and within educational institutions. The purpose of this paper is to identify the personal traits of the analyzed managers and what leadership styles they have. However, through this paper we try to answer questions like: Who are managers and what qualities they must have? Based on both quantitative and qualitative methods, this paper consists in an exploratory research, by highlighting the relevant information in the field. The fact is that a manager is the main pawn in an organization. On his professional training, management, and psycho-behavioral depends the smooth running of the organization.